Foreign exchange black markets in Latin America (Praeger, 1994)
"Examines how and why foreign exchange black (i.e., parallel) markets function, as well as their economic impact. Includes case studies for Argentina, Brazil, Colombia, Jamaica, and Peru. Valuable contribution represents one of the few in-depth studies of this topic"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/